Ocular Perfusion Pressure in Primary Open Angle: Doi: 10.36351/pjo.v40i3.1746 - Khan, Bakht Samar; Iqbal, Saleem; Danyal Khan, Bakht; Irshad, Zubeda; Ullah, Imdad (Pakistan Journal of Ophthalmology, 2024)
Purpose: To determine thecorrelation of Mean Ocular Perfusion Pressure (MOPP) with Mean Arterial Pressure (MAP) in primary open angle glaucoma (POAG)and normal tension glaucoma. Study Design: Cross sectional study. Place and Duration of Study: Khyber Teaching hospital, Peshawar from July, 2017 to December, 2019. Methods: A total of 375 patients with POAG were admitted in the hospital. Patients with variable blood pressure (BP) on admission or history of blood pressure or using anti-hypertensive drugs were selected. Patients with secondary Glaucoma, Primary Angle closure Glaucoma, patients with Diabetes mellitus and age below 40 years were excluded. Finally,200 patients were recruited by convenience sampling. Forty-eight hours monitoring of MAP and Intra ocular pressure (IOP) phasing were done. MAP, MOPP and peak IOP were charted. Results: MAP and MOPP variabilitywas observed in 53% of patients with POAG. The Pearson co-relation coefficient for those patients in which intervention had yet not been done was -0.460 suggesting a moderate negative correlation between MOPP and IOP (p value <0.01). In IOP controlled patients, the coefficient was -0.346 (p<0.01). Theresults showed a negative correlation between the two values in both data sets. The correlation co-efficient for MAP and IOP in both pre-admission and controlled IOP patients showed strong positive correlation (0.816 and 0.854 respectively for two tailed tests with 0.01 significance). Conclusion: MOPP, MAP and IOP are correlated and their determination is important in all Primary Open Angle Glaucoma particularly in Normal Tension Glaucoma.